Post graduate supervision: a comparative study between Malaysia and the United Kingdom / Gurnam Kaur Sidhu, Chan Yuen Fook and Farhana Wan Yunus - Kaur Sidhu, Gurnam; Chan, Yuen Fook; Wan Yunus, Farhana (2012)
The twin forces of globalisation and internationalisation brought about the democratisation and masssification of education which has led to greater equity and access to higher education. This witnessed a sharp increase in post graduate programmes especially in institutions of higher learning. Such expansion led to increasing demand for greater accountability in post graduate supervision. Henceforth, this study sought to investigate post graduate supervision in Malaysia and the United Kingdom. The study involved two public universities from Malaysia and two universities from the United Kingdom. A total of two social science faculties were involved from each university. The final sample consisted of 99 post graduate respondents and 12 supervisors. This descriptive research study employed a mixed method which entailed the use of a questionnaire and semi structured interviews. The findings revealed that though there were no significant differences with regards to supervisory practices of supervisors in Malaysia and the United Kingdom, significant differences were exhibited with regards to supervisees’ perceptions of supervisors’ roles and responsibilities, their level of support and guidance, their leadership characteristics, institutional support and post graduate challenges. Respondents also indicated that UK supervisors displayed better leadership characteristics than their counterparts in Malaysia. Findings also revealed that the supervisees in the UK exhibited greater autonomy and were seen as more mature and independent learners with fewer expectations from their supervisors. In contrast, the Malaysian post graduate supervisees were seen as less independent and hence had higher expectations of their supervisors. Malaysian supervisees also focussed more on the ‘person’ and personality factors, compared to the UK respondents who centred more on the academic expertise and professional ethics of supervisors. These findings imply that post graduate supervision in both countries especially Malaysia called for a more critical look into further clarifying the roles and responsibilities of supervisors, more effective supervisory practices and providing more help and guidance in terms of institutional support and focussed training for post graduate supervisors and supervisees.